Anthocyanin Pigments of Siahe Sardasht Grapes (Journal of Sciences, Islamic Republic of Iran)
The anthocyanins of Siahe Sardasht variety (Vitis vinifera L. var. S.S.) were extracted from freezed samples and were purified by adsorption on cation-exchange resin column. Individual pigments were separated by TLC on cellulose plates. Monomeric anthocyanin content that was determined by pH-differential, was 1740.11±3.58 mgL?1 (based on malvidin 3-glucose). Five major pigments were identified by 1H-NMR, IR and UV-Visible spectroscopies. All pigments were acylated with acetyl groups and three of them were acylated with malonyl groups